Penguatan Literasi Anak Usia Dini Melalui Penyediaan Buku Bacaan Edukatif - Cahyaningrum, Dinis; Hasany, Tifani Dame; Safitri, Dhanny; Muhtarom, Zamroni Alpian; Girsang, Zefanya Andryan (LPPM Universitas PGRI Argopuro Jember, 2026)
Early childhood literacy is a fundamental foundation for supporting children’s language, cognitive, social, and emotional development. However, limited literacy facilities, particularly the availability of educational reading books appropriate to children’s developmental stages, remain a challenge in several preschool (PAUD) institutions. This community service activity aimed to strengthen preschool literacy through the provision of educational reading books at TK Maca Pasir Putih, Pemenang District, North Lombok Regency. The activity was implemented participatively in three stages: preparation (observation and discussion with partners), implementation (provision and utilization of educational books in learning activities), and evaluation (observation and discussion with teachers). The results indicated an increase in children’s reading interest and engagement in literacy activities. Children showed greater enthusiasm in reading, storytelling, and vocabulary recognition. Teachers also stated that the books supported daily lesson plans (RPPH), enabling better integration of literacy into thematic learning. Overall, this activity contributed positively to improving the quality of preschool.